Comparison of Two Models for Radiative Heat Transfer in High Temperature Thermal Plasmas. (9th August 2011) - Melot, Matthieu; Trépanier, Jean-Yves; Camarero, Ricardo; Petro, Eddy
Abstract : Numerical simulation of the arc-flow interaction in high-voltage circuit breakers requires a radiation model capable of handling high-temperature participating thermal plasmas. The modeling of the radiative transfer plays a critical role in the overall accuracy of such CFD simulations. As a result of the increase of computational power, CPU intensive methods based on the radiative transfer equation, leading to more accurate results, are now becoming attractive alternatives to current approximate models. In this paper, the predictive capabilities of the finite volume method (RTE-FVM) and the P1 model are investigated. A systematic comparison between these two models and analytical solutions are presented for a variety of relevant test cases. Two implementations of each approach are compared, and a critical evaluation is presented.